A Promising Teacher Training Model for Rural Settings - Dyck, Norma J.; Thurston, Linda P. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
A training model to prepare practicing teachers in rural areas as special educators is described. Developed at Kansas State University, the model employs a multi-modal approach which combines a variety of long-distance teaching methods with traditional on-campus summer course work. The model incorporates the use of an interactive audio telecommunications network, independent study, and field experiences that allow students to apply their newly learned skills in the settings where they work. Each training cycle is conducted over a spring-summer-fall time span. During the spring semester, participants attend an on-campus conference, read selected materials, and participate in several teleconferences. The content of the teleconferences ranges from discussion of reading assignments to guest speaker presentations or a networking of experts from locations anywhere in the country. Summer activities include traditional courses on campus and simulated lab experiences. During the fall semester, teachers apply new skills in the school districts where they are employed, with the assistance of a local collaborator who provides advice and feedback. Teleconferences link students with university resources for problem-solving. A final drive-in conference is held near the end of the semester. Evaluation methods include student self-assessment on a continuing basis through keeping logbooks. (Author/JW)
ERIC Note: Paper presented at the Council for Exceptional Children's Topical Conference on the Future of Special Education (Orlando, FL, November 15-17, 1987).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Demonstration Programs; Distance Education; Inservice Teacher Education; Models; Professional Development; Rural Schools; Special Education; Teacher Education Curriculum; Teacher Education Programs; Teacher Evaluation; Teacher Recruitment; Teacher Supervision; Teacher Supply and Demand; Teleconferencing; Reports, Descriptive; Speeches/Meeting Papers